Nilai Budaya Minangkabau dalam Cerpen "Cimuntu Lansie" Karya Wisran Hadi - Suhardi, Suhardi (Jurnal Bahasa Lingua Scientia, 2018)
The current era of globalization from one side has a positive effect. But from the other side it also brings negative effects (cultural crisis), that is, the emergence of bad behavior of a group of people (irrelevant to cultural values ââwhich is followed until now). This research is more focused on the study of Minang cultural values ââin the short story "CimuntuLansie" written by WisranHadi. This research uses a descriptive method. The data collection was done by using literature study method. And the data analysis applied the Miles and Huberman model(1992), with the following steps: (1) identification of WisranHadiâs short story as the research object, (2) data reduction, (3) data presentation, (4) data interpretation based on the relevant theories, and (5) making conclusion. The obtained result of data analysis is the short story CimuntuLansie by WisranHadi contains Minang cultural values, such as: (1) religion, (2) honesty, (3) tolerance, (4) discipline, (5) democracy, (6) communicative, (7) love and peace, (8) social, and value (9) responsibility. These values ââare the basic values ââhighly respected in the Minangkabau society in everyday life. WisranHadi as writer of this short storyhas encouraged people to return to cultural values ââthat are highly upheld during this time.